Chloroplastic ATP Synthase Alleviates Photoinhibition of Photosystem I in Tobacco Illuminated at Chilling Temperature - Yang, Ying-Jie; Zhang, Shi-Bao; Huang, Wei (Frontiers in Plant Science, 2018)
Chloroplastic ATP synthase plays an important role in the regulation of proton motive force and proton gradient (ΔpH) across the thylakoid membranes. However, the regulation of chloroplastic ATP synthase at chilling temperature and its role in photoprotection are little known. In our present study, we examined the chlorophyll fluorescence, P700 signal and electrochromic shift signal at 25ºC and 6ºC in tobacco (Nicotiana tabacum L. cv. Samsun). Although photosynthetic electron flow through both PSI and PSII were severely inhibited at 6ºC, non-photochemical quenching and P700 oxidation ratio were largely increased. During the photosynthetic induction under high light, the formation of proton motive force at 6ºC was similar to that at 25ºC. However, the ΔpH was significantly higher at 6ºC, owing to the decreased activity of chloroplastic ATP synthase (gH+). During illumination at 6ºC and high light, a high ΔpH made PSI to be highly oxidized, preventing PSI from photoinhibition. These results indicate that the down-regulation of gH+ is critical to the buildup of ΔpH at low temperature, adjusting the redox state of PSI and thus preventing photodamage to PSI. Our findings highlight the importance of chloroplastic ATP synthase in photoprotection at chilling temperature.